2021
DOI: 10.1002/jcu.23053
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of nomograms for fetal vermis and brainstem structures in the midsagittal cranial plane by ultrasonography

Abstract: Purpose To construct nomograms for the fetal cerebellar vermis and brainstem structures obtainable from the midsagittal plane of the brain by two‐dimensional sonography. Methods This was a prospective cross‐sectional study of 434 healthy fetuses in low‐risk singleton pregnancies between 18 and 35 gestational weeks. The following parameters were evaluated in the midsagittal cranial plane; cerebellar vermis anteroposterior diameter (APD), craniocaudal diameter (CCD), pons, midbrain and medulla oblongata APD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…For example, Rizzo et al [ 11 ] established reference limits for the cerebellar vermis using three-dimensional ultrasonography images. Alpay et al [ 12 ] constructed nomograms for brainstem structures using two-dimensional ultrasonography (2D-US). A study by Chang et al [ 13 ] demonstrated the effectiveness of three-dimensional ultrasound in assessing fetal cerebellar volume throughout normal gestation, leading to the development of volume-based nomograms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rizzo et al [ 11 ] established reference limits for the cerebellar vermis using three-dimensional ultrasonography images. Alpay et al [ 12 ] constructed nomograms for brainstem structures using two-dimensional ultrasonography (2D-US). A study by Chang et al [ 13 ] demonstrated the effectiveness of three-dimensional ultrasound in assessing fetal cerebellar volume throughout normal gestation, leading to the development of volume-based nomograms.…”
Section: Introductionmentioning
confidence: 99%